A case-control study of menstrual dysfunction occurring in women attending a general practice after tubal ligation - Kruger, Breslau (Department of Public Health and Family Medicine, 2018)
Tubal sterilization is the world's most popular contraceptive method. The possibility of subsequent menstrual dysfunction has been a cause for concern. This study was conducted to examine whether post-sterilisation menstrual dysfunction was measurable in a group of women attending a general practice, by means of a case-control study. Biopsychosocial factors, such as health status, social support, psychological and medical history, and reasons for sterilisation were investigated to see whether any of these factors could be predictive of post-sterilisation menstrual problems. Sterilised women attending a general practice over an eight-month period were invited to participate in the study. 143 out of 144 patients completed a highly structured interview (questionnaire) administered by two interviewers. Forty-nine cases were identified and compared to ninety-four controls. The results showed that women with menstrual dysfunction differed from a comparison group in that; those with menstrual dysfunction were generally less satisfied with their quality of life, had significantly more fears about sterilisation, felt that the quality of their social support was inferior, and suffered from depression and tension headaches more often than controls. Menstrual dysfunction was also more common during the first two years after tubal ligation. These results could point to factors other than biological factors involved in menstrual dysfunction following tubal ligation.